A Multigrid Method for Nonlinear Parabolic Problems (Journal of Computational Mathematics, 2021)
The multigrid algorithm in [13] is developed for solving nonlinear parabolic equations arising from the finite element discretization. The computational cost of the algorithm is approximate $O(N_kN)$ where $N_k$ is the dimension of the finite element space and $N$ is the number of time steps.